Need frustration and depressive symptoms in French older people: using a self-determination approach. (27th May 2021) - Ferrand, Claude; Martinent, Guillaume
Abstract: Objectives: To provide evidence of the relationship between basic psychological need frustration (BPNF) for autonomy, competence and relatedness, and depressive symptoms in French older people, and to explore the potential moderator effects of place of residence (home vs nursing home) on this relationship. Methods: Partial least squares path modeling (PLS-PM) was used. A total of 410 French older people (212 women, 198 men, M age = 77.13 years, SD  = 9.19, age range: 60-98 years) voluntarily participated in the study and completed the measures of BPNF and depressive symptoms. Sociodemographic data were collected. Results: Findings showed that for all the participants, competence and relatedness need frustration positively predicted depressive symptoms. More particularly, BPNF for relatedness significantly predicted depressive symptoms for older people living at home ( β = .18, p < .05), whereas BPNF for competence significantly predicted depressive symptoms for both participants living at home ( β = .25, p < .05) and in nursing homes ( β = .34, p < .05). Among participants living at home, results showed that BPNF for competence significantly predicted depressive symptoms ( β = .28, p < .05) across married participants, while BPNF for relatedness significantly predicted depressive symptoms ( β = .27, p < .05) across participants living alone. Conclusion: By focusing on BPNF and its relationship to depressive symptoms, this study suggests the importance of investigating further this concept, and alerts to the long-term consequences of frustration of competence and relatedness needs in older people.